1999
DOI: 10.1034/j.1600-0420.1999.770404.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Octreotide on experimental corneal neovascularization

Abstract: ABSTRACT.Purpose:To examine the ability of subcutaneously administered Octreotide ( a long acting somatostatin analoque) to serve as an inhibitory agent for corneal neovascularization in eyes of Wistar Albino rats. Methods: Neovascular growth into the corneas of all the animals was induced by silver nitrate cauterization. Half of the animals which were randomly selected for the Octreotide group received 30 micrograms systemic Octreotide for 7 days. The treatment was initiated on the same day as chemical cauter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
0
8
0
1
Order By: Relevance
“…We used toluidine blue staining as a molecular method to detect neovascularization. 27,28 After injury, the experimental control group showed more neovascular growth (Figures 5b and d) Table 1. Seven days after one-injection treatment of GABPa/b or empty plasmid DNA, the mean neovascular area and the mean number of vessels in three corneal sections of each mouse in GABP-treated eyes were significantly less than those in empty-vector-treated eyes (Po0.01 and o0.05, respectively) and experimental control eyes (Po0.01 and o0.05, respectively).…”
Section: Quantitative Biomicroscopic Analysis Shows Less Neovascularimentioning
confidence: 93%
See 1 more Smart Citation
“…We used toluidine blue staining as a molecular method to detect neovascularization. 27,28 After injury, the experimental control group showed more neovascular growth (Figures 5b and d) Table 1. Seven days after one-injection treatment of GABPa/b or empty plasmid DNA, the mean neovascular area and the mean number of vessels in three corneal sections of each mouse in GABP-treated eyes were significantly less than those in empty-vector-treated eyes (Po0.01 and o0.05, respectively) and experimental control eyes (Po0.01 and o0.05, respectively).…”
Section: Quantitative Biomicroscopic Analysis Shows Less Neovascularimentioning
confidence: 93%
“…16 To determine the degree of induced angiogenesis, we stained sections with toluidine blue. 27,28 Three representative sections obtained from each cornea of experimental control, empty-vector-treated or GABPa/b-treated groups were analyzed with a microscope (Olympus, Tokyo, Japan) as described. 16 The images were captured with a Spot digital camera (Media Cybernetics) and morphometric analyses were performed using ImagePro Plus software.…”
Section: Analysis Of Corneal Neovascularization By Histologic Examinamentioning
confidence: 99%
“…As the half-life of the native hormone in the blood stream is only 1±3 min, the effects are best seen when analogues with longer half-lives are used, and when the release mechanism for one of the affected hormones is markedly elevated, such as a pituitary adenoma with increased secretion of GH in acromegaly. Somatostatin agonist analogs have also been shown to be anti-angiogenic in vitro (Grant et al, 1993;Danesi and Del Tacca, 1996;Danesi et al, 1997) and in vivo (Woltering et al, 1991;Barrie et al, 1993;Patel et al, 1994;Baudouin et al, 1995;Demir et al, 1999). This activity involves inhibition of endothelial cell proliferation (Grant et al, 1993;Danesi and Del Tacca, 1996;Danesi et al, 1997) and may result in the inhibition of tumor growth via inhibition of blood vessel growth (Woltering et al, 1991).…”
Section: Introductionmentioning
confidence: 90%
“…3 Other studies have shown that thalidomide, curcumin, integrin antagonists, cyclooxygenase inhibitors, prolactin, octreotide, herbal extracts, matrix metalloproteinase inhibitors, angiostatic steroids, thrombospondin-2, kringle 1-3, and beta-cyclodextrin tetradecasulfate all exert inhibitory effects on the development of corneal neovascularization induced by various methods. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Our study demonstrates the ability of angiostatin to inhibit neovascularization in a clinically relevant model of mechanical and chemical corneal trauma. The method of neovascularization induction affects pharmacological efficacy, eg, integrin antagonists inhibit basic fibroblast growth factorinduced corneal neovascularization but not that caused by chemical injury.…”
Section: Statisticsmentioning
confidence: 98%